ANALYSIS OF DIRECT METHOD IN LEARNING MAHARAH KALAM IN JUNIOR HIGH SCHOOL OF TAHFIDZ AL-QUR'AN BOARDING SCHOOL DARUL QOLAM BINJAI-NORTH SUMATERA - Pane, Fazrin Aulia; Salamuddin, Salamuddin (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This study examines the use of the direct method in teaching maharah kalam (speaking skills) at SMP Pondok Pesantren Tahfizh Al-Qur'an Darul Qolam Binjai, focusing on its implementation, strengths, and weaknesses. Using a descriptive qualitative case study approach, data were collected through observation, interviews, and documentation. The participants were students involved in the maharah kalam program, with the focus on how the direct method was applied in instruction. Findings show that the method encourages active Arabic speaking, boosts students' confidence, and supports contextual learning. Its advantages include enhancing speaking and listening skills, increasing motivation, and fitting the pesantren environment. However, challenges include the need for skilled teachers, difficulties for beginners, limited instructional time, and a lack of technological support. Improving this method's effectiveness requires better teacher training and innovative learning strategies.